Implementasi Pemasaran Digital pada Media Sosial Instagram Deustchkursebildung - Thabina Carissa Putri; Hudi Santoso (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study discusses the implementation of digital marketing strategies through Instagram social media on the deutschkursebildung account, this company is engaged in German language education. The purpose of this study is to describe the digital marketing strategy carried out by deutschkursebildung through Instagram. The method used is a qualitative descriptive approach with data collection through Instagram account observations, interviews, and documentation. The results of the study show that the use of attractive visual content, consistency in uploads, and active interaction with followers have a positive impact on increasing audience engagement. Thus, digital marketing strategies through Instagram have proven to be an effective tool in supporting the growth and existence of deutschkursebildung in the digital era.